Biomarker-guided preemption of steroid-refractory graft-versus-host disease with alpha-1-antitrypsin - Gergoudis, Stephanie C.; Defilipp, Zachariah; Ozbek, Umut; Sandhu, Karamjeet S.; Etra, Aaron M.; Choe, Hannah K.; Kitko, Carrie L.; Ayuk, Francis; Aziz, Mina; Baez, Janna; Ben-David, Kaitlyn; Bunworasate, Udomsak; et al. (Blood Advances, 2020)
Steroid-refractory (SR) acute graft-versus-host disease (GVHD) remains a major cause of nonrelapse mortality (NRM) after allogeneic hematopoietic cell transplantation (HCT), but its occurrence is not accurately predicted by pre-HCT clinical risk factors. The Mount Sinai Acute GVHD International Consortium (MAGIC) algorithm probability (MAP) identifies patients who are at high risk for developing SR GVHD as early as 7 days after HCT based on the extent of intestinal crypt damage as measured by the concentrations of 2 serum biomarkers, suppressor of tumorigenesis 2 and regenerating islet-derived 3 alpha. We conducted a multicenter proof-of-concept "preemptive" treatment trial of alpha-1-antitrypsin (AAT), a serine protease inhibitor with demonstrated activity against GVHD, in patients at high risk for developing SR GVHD. Patients were eligible if they possessed a high-risk MAP on day 7 after HCT or, if initially low risk, became high risk on repeat testing at day 14. Thirty high-risk patients were treated with twice-weekly infusions of AAT for a total of 16 doses, and their outcomes were compared with 90 high-risk near-contemporaneous MAGIC control patients. AAT treatment was well tolerated with few toxicities, but it did not lower the incidence of SR GVHD compared with controls (20% vs 14%, P = 5.56). We conclude that real-time biomarker-based risk assignment is feasible early after allogeneic HCT but that this dose and schedule of AAT did not change the incidence of SR acute GVHD. This trial was registered at www.clinicaltrials.gov as #NCT03459040.
CRIS-Team WoS Importer:2021-01-15